Balancing of assembly lines with collaborative robots - Christian Weckenborg; Karsten Kieckhäfer; Christoph Müller; Martin Grunewald; Thomas S. Spengler (Business Research, 2020)
Motivated by recent developments to deploy collaborative robots in industrial production systems, we investigate the assembly line~balancing problem with collaborative robots. The problem is characterized by the possibility that human and robots can simultaneously execute tasks at the same workpiece either in parallel or in collaboration. For this novel problem type, we present a mixed-integer programming formulation for balancing and scheduling of assembly lines with collaborative robots. The model decides on both the assignment of collaborative robots to stations and the distribution of workload to workers and robotic partners, aiming to minimize the cycle time. Given the high problem complexity, a hybrid genetic algorithm is presented as a solution procedure. Based on extensive computational experiments, the algorithm reveals promising results in both computational time and solution quality. Moreover, the results indicate that substantial productivity gains can be utilized by deploying collaborative robots in manual assembly lines. This holds especially true for a high average number of robots and tasks to be assigned to every station as well as a high portion of tasks that can be executed by the robot and in collaboration.
Keywords: 650; Industry 4.0; Assembly line balancing; Assembly line configuration; Human-robot collaboration; Cobots